EFEKTIVITAS PENGELOLAAN TAMAN PENITIPAN ANAK (TPA) DI SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Dwi Mairiza Putri; Desti Irja; Aswandi Bahar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The formulation of problem in this research is "How is the effectiveness of the management of child care park (TPA) in Learning Activity Center (SKB) Pekanbaru City". This research uses a descriptive naturalistic research with qualitative approach which aims to provide a systematic description of the effectiveness of the management of child care (TPA) in Pekanbaru City Learning Activity Studio. This research consist of one variable that is effectiveness with research indicator that is (1) Achievement of TPA management goal, (2) Determining target in TPA management, (3) Availability of resources supporting TPA management, (3) Implementation of main duty of TPA . The subjects of this study were 5 informants ie 1 core informant, 2 control informants, and 2 informant observers. Data collection techniques is to make observations, interviews, and documentation. Based on the results of interviews with informants, the researchers found data that through the 3 indicators is clear that the effectiveness of management in the TPA in Learning Activity Center (SKB) Pekanbaru City is the managers who are able to carry out their respective roles as managers TPA. Foster children who dititpkan not just dititpkan, but also given the activities - activities that are positive. Able to overcome the obstacles that exist. Establish communication with foster parent's parents to see the progress of the foster children. Have adequate facilities and infrastructure. Build cooperation and create good coordination among managers. There is an evaluation or assessment carried out by directly monitoring or directly monitoring both the performance of managers and caregivers and also foster children.Keywords: Effectiveness, Management, Childcare Park (TPA).